2000
DOI: 10.1042/0264-6021:3460767
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric regulation of neuronal nitric oxide synthase by tetrahydrobiopterin and suppression of auto-damaging superoxide

Abstract: The underlying mechanisms regulating the activity of the family of homodimeric nitric oxide synthases (NOSs) and, in particular, the requirement for (6R)-5,6,7,8-tetrahydro-L-biopterin (H(4)Bip) are not fully understood. Here we have investigated possible allosteric and stabilizing effects of H(4)Bip on neuronal NOS (NOS-I) during the conversion of substrate, L-arginine, into L-citrulline and nitric oxide. Indeed, in kinetic studies dual allosteric interactions between L-arginine and H(4)Bip activated recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…The enhancement of oxidative stress as a result of NOS uncoupling could exacerbate NOS dysfunction by destabilizing the quaternary structure of the NOS dimers, causing them to dissociate into their nonfunctional monomeric forms [31], [32]. In the present study, increased levels of eNOS and nNOS monomerization indicate that enhanced conformational inactivation of eNOS and nNOS under conditions of elevated oxidation stress in the brain could contribute to NOS dysfunction in ECM.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The enhancement of oxidative stress as a result of NOS uncoupling could exacerbate NOS dysfunction by destabilizing the quaternary structure of the NOS dimers, causing them to dissociate into their nonfunctional monomeric forms [31], [32]. In the present study, increased levels of eNOS and nNOS monomerization indicate that enhanced conformational inactivation of eNOS and nNOS under conditions of elevated oxidation stress in the brain could contribute to NOS dysfunction in ECM.…”
Section: Discussionmentioning
confidence: 55%
“…Functional NOS dimers can become unstable and dissociate into their nonfunctional monomeric forms under conditions of enhanced oxidative stress [31], [32]. We asked if enhanced conformational inactivation of NOS isoforms by monomerization could contribute to NOS dysfunction in the brain during ECM development.…”
Section: Resultsmentioning
confidence: 99%
“…Decreased BH4 bioavailability leads to conformational changes in the NOS homodimer, leading to the phenomenon known as NOS-uncoupling, where less NO is generated and instead the enzyme produces superoxide [6]. Studies in the heart and vasculature have shown BH4 deficiency or its oxidation to BH2 increases NOS-derived reactive oxygen species (ROS) generation.…”
Section: Introductionmentioning
confidence: 99%
“…So, it may be that L-Arg supplementation enhances NOS activity decreasing ROS formation. This may explain the increase in NOS activity in the diabetic rats, but not in the control rats, which led us to think that L-Arg is more probably acting as an allosteric activator of the enzyme in both control and diabetic rats [45].…”
Section: Discussionmentioning
confidence: 95%